PENGGUNAAN MEDIA FLIPBOOK DALAM MENINGKATKAN KEMAMPUAN MEMBACA SISWA SEKOLA DASAR - Khairina, Aisyah; Nasution, Sahkholid (STIT AL MULTAZAM, 2024)
Flipbook media is the right media to use in improving students' reading skills in elementary schools because the majority of students are not yet able to think abstractly about the material being taught, but instead need to visualize the material being taught. The aim of this research is to describe the process of using Flipbook media which can improve the reading skills of students in elementary schools. This research uses a qualitative approach with descriptive methods. Data collection techniques use observation and interview techniques. The researcher made observations first to observe the students' learning process, especially in learning Indonesian, starting from planning, media use, to media evaluation. Then, researchers conducted interviews with class teachers and class 1 students to determine the level of effectiveness of using Flipbook media. The subjects in this research were, Class 1 Educators at SDN 152981 TUKKA 1A, Head of SDN 152981 TUKKA 1A and all 28 Class 1 students. The results of the research revealed that grade 1 students at SDN 152981 TUKKA 1A had difficulties in reading, namely difficulties in recognizing letters, recognizing syllables, reading words without spelling, and difficulty in reading short sentences. The use of Flipbook media in improving reading skills at SDN 152981 TUKKA 1A includes the planning process, media use process and learning media evaluation process. After observations made by researchers from the results of using Flipbook interactive media, it showed that the reading ability of class 1 students at SDN 152981 TUKKA 1A had increased very significantly